CO-BRANDING PARTNERSHIPS IN THE DIGITAL LANDSCAPE: DRIVING CONSUMER VALUE CREATION AND TRUST - Yohanes Sriwomatu (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
The rapid development of digital technologies has transformed the way companies design marketing strategies and build relationships with consumers. One of the emerging strategies widely adopted in the digital economy is co-branding partnerships, where two or more brands collaborate to create products, services, or experiences that combine their respective strengths. This study aims to examine the role of co-branding partnerships in the digital landscape in driving consumer value creation and consumer trust. The research employs a qualitative approach using library research, which analyzes relevant academic literature obtained from reputable databases such as Scopus, Web of Science, and Google Scholar. Through thematic and conceptual analysis, this study synthesizes prior research on co-branding strategies, digital marketing ecosystems, consumer value creation, and brand trust. The findings indicate that co-branding partnerships play a strategic role in enhancing consumer value by combining complementary brand attributes, technological capabilities, and market reach. In digital environments characterized by high consumer interaction and transparency, collaborative branding strategies can increase perceived value, strengthen consumer engagement, and foster stronger trust toward brands. However, the effectiveness of co-branding initiatives largely depends on the compatibility and alignment between collaborating brands. Partnerships that lack strategic congruence may weaken brand credibility and reduce consumer confidence. This study contributes to the marketing literature by integrating co-branding partnerships, consumer value creation, and consumer trust within a digital marketing framework. Practically, the study offers insights for firms seeking to design effective brand collaboration strategies that enhance consumer trust and sustainable competitive advantage in the digital marketplace.